The effect of tilapia Oreochromis niloticus addition on the sediment of brackish low-salinity ponds to white shrimp Penaeus vannamei farming system during the wet and dry season - Juárez-Rosales,Jorge (Pontificia Universidad Católica de Valparaíso. Facultad de Recursos Naturales. Escuela de Ciencias del Mar, 2020)
ABSTRACT The present study was carried out to determine the effect of tilapia Oreochromis niloticus on the physical and chemical sediment parameters on an earthen pond in monoculture (shrimp Penaeus vannamei) and co-culture (tilapia-shrimp) during the dry and wet seasons in a commercial farm during the period from mid-September to end-December 2017 and February to mid-May 2018. Chemical and physical analyses were realized on sediment samples from brackish water ponds representing shrimp farms in San Blas Nayarit, Mexico. Concentrations of organic carbon, nitrogen, potassium, magnesium and calcium were higher in co-culture ponds, and there was a tendency to a higher concentration of phosphorus and sodium in the sediment of monoculture ponds. The texture of the ponds showed a tendency in the dry season to increase the percentage of clay in co-culture due to the effect of bioturbation caused by tilapia. There was no evidence of poor development of sediment quality in any treatment. It was found that tilapia was a factor that affected sediment quality, differences in growth between shrimp monoculture and tilapia-shrimp co-culture can be explained, at least in part, by differences in their sediment.